Commentary on Drash and Tudor: An analysis of autism as a contingency-shaped disorder of verbal behavior - Romanczyk, Raymond G. (2004)
A critique is presented of the etiological model for autism as presented by Drash and Tudor. The model is rejected based upon conceptual and methodological grounds. The major points raised concern overgeneralization of research findings, limitations of single subject methodology to answer population based questions, current neurobiological research, and the danger of uni-dimensional models. Specific examples of cases that do not fit Drash and Tudor model are presented.